QUALITY OF SERVICE AT THE PERSONNEL AND HUMAN RESOURCES DEVELOPMENT AGENCY OF SOUTHEAST MINAHASA REGENCY - Rieske B. Palad; William Areros; Evelin J.R. Kawung (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The goal of this research is to assess the service quality of the Personnel and Human Resources Development Agency in Southeast Minahasa Regency. The researchers used a qualitative descriptive approach with a focus on responsiveness, responsibility, and accountability. The study was conducted with six informants, and data was collected through observation, interviews, and documentation. The data was analyzed through three stages: data reduction, data presentation, and data verification. The findings indicate that the staff at the agency were responsive in providing administrative services, but the filing process was slow due to leadership dispositions and uncertainty in management. The agency showed responsibility in executing administrative processes and was accountable in accordance with predetermined processes and standard operating procedures. Overall, the study concludes that the quality of services provided by the agency is responsive to the needs of civil servants, but improvements are needed in terms of openness in management and the speed of the filing process.